Economic instruments in environmental protection in Denmark (Ministry of Environment and Energy, 1999)
This report provides a comprehensive and up-to-date statut on the current use of economic instruments in Danish environment protection. The report focuses on the implementation and enforcement aspects of the Danish experience.